2014
DOI: 10.1111/jch.12427
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Is Significantly Associated With Cardiovascular Disease Risk Factors in 2‐ to 9‐Year‐Olds

Abstract: The objective of this analysis was to estimate the prevalence of cardiovascular disease risk factors in ethnically diverse 2-to-9 year olds. A retrospective medical chart review identified overweight/obese 2-to-9 year olds (N=147) from a local pediatric clinic who were matched (on age, sex and ethnicity) to normal weight subjects from the 2005–2010 National Health and Nutrition Examination Surveys (NHANES) (N=294). Comparisons of mean systolic (SBP) and diastolic (DBP) blood pressure, total- and high density l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Regarding wound infection, the association between elevated BMI (>30kg/m 2 ) and infection in pediatric spine surgery has been shown [12]. Unfortunately, even in children, obesity is known to be associated with cardiovascular risk factors such a diastolic pre-hypertension, systolic pre-hypertension, and low high-density lipoprotein in 2–9 year olds [13], which is echoed in other large population-based cohorts [14]. …”
Section: Discussionmentioning
confidence: 99%
“…Regarding wound infection, the association between elevated BMI (>30kg/m 2 ) and infection in pediatric spine surgery has been shown [12]. Unfortunately, even in children, obesity is known to be associated with cardiovascular risk factors such a diastolic pre-hypertension, systolic pre-hypertension, and low high-density lipoprotein in 2–9 year olds [13], which is echoed in other large population-based cohorts [14]. …”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerotic cardiovascular disease (ASCVD) remains the leading cause of morbidity and mortality worldwide [1]. Although primarily a disease of adults, youth with obesity show evidence of subclinical ASCVD [13] which places them at increased risk as adults for coronary heart disease [2] and stroke [4].…”
Section: Introductionmentioning
confidence: 99%
“…62 A study of obese children aged 2 to 9 years, compared with normal-weight children, found higher SBPs, higher diastolic BPs, and a significantly higher prevalence of the lowest quintile of high-density lipoprotein cholesterol. 63 Despite the negative attitude of the USPSTF, these findings should also add to the consideration of careful lifestyle changes in such children even in the absence of randomized controlled clinical trial evidence. This difficult and controversial area will likely be a battleground for some time to come, because surely it is in children and young adults where there might be the greatest opportunity to favorably affect the lifelong trajectory of vascular disease.…”
Section: Clinical Practice and Guidelinesmentioning
confidence: 98%
“…One of the major factors in childhood hypertension is obesity, including in children younger than 10 years . A study of obese children aged 2 to 9 years, compared with normal‐weight children, found higher SBPs, higher diastolic BPs, and a significantly higher prevalence of the lowest quintile of high‐density lipoprotein cholesterol . Despite the negative attitude of the USPSTF, these findings should also add to the consideration of careful lifestyle changes in such children even in the absence of randomized controlled clinical trial evidence.…”
Section: Clinical Practice and Guidelinesmentioning
confidence: 99%